IMPLIKASI MODERNISASI TEKNOLOGI PERIKANAN TERHADAP MASYARAKAT PANTAI (Kasus Nelayan Orang Bugis di Kota Bontang Kalimantan Timur) - Badruddin Nasir (Universitas 17 Agustus 1945 Samarinda, 2022)
Fishing communities generally live in coastal areas and are a social group whose lives are often relatively low. The low level of social life of fishing communities by many observers, the cause of which is often blamed on the mentality factor of fishermen as fishermen as fishermen by cultivating open land. The development in the field of fisheries that is carried out with reference to the modernization assumption that development must move forward in the sense that the life of fishermen should be better than before. The government's concern is in its efforts to improve the fate of fishermen by changing the fishing system from traditional to modern ways through a motorization program which is a prodak of modernization in the hope of changing the level of welfare of fishing communities. The method used in this study is a descriptive method with a qualitative approach. descriptive research aims to describe exactly the traits of a particular individual, circumstance, symptom, or group. The data sources in this study are in accordance with the required data, namely primary data and secondary data. Data collection is carried out by means of observation or direct observation in the field, this technique is carried out by directly observing the phenomena that occur in the field according to the subject matter under study, then in-depth interviews. The results of this study, namely the application of motorization to fishing communities did not get good results because what could change their level of life was only financiers or juragans while working fishermen did not get an improvement in the quality of life, the cause was because fishermen had a mentality that was betting on fate, there was a pattern of relationships between mustard ponggawa or client patrons in their work system, and the profit-sharing system that was applied only based on the agreement but the determinant is from the ponggawa or patron. In general, it can be seen that with the motorization implemented by the Bontang city government, the Bugis people can change their mindset and lifestyle towards a modern fishing community that is always forward-oriented and thinks rationally to be able to change their standard of living towards achieving a better level of welfare.